DEVELOPING THE 21ST CENTURY SKILLS IN ESSAY WRITING COURSE DURING THE COVID-19 PANDEMIC - Siti Nuridayanti; Sarah Aqila; Diani Nurhajati (UMBanjarmasin, 2021)
In the 21st-century, the development of science and technology encourages humans to overcome fast changes. The role of education influences the quality of the young generation. They must be equipped with 21st-century skills, namely creativity, critical thinking, collaboration, and communication (4Cs). However, the COVID-19 Pandemic change the process of teaching and learning. Teachers have to think over the appropriate teaching strategy to facilitate students developing 4Cs. This research aims to describe the learning process of the Essay Writing course using Project Based Learning to train the skills of 4Cs in the University of Nusantara PGRI Kediri during the COVID-19 Pandemic. The research used a qualitative approach. Data sources came from the lecturer and the students who took this course. The lecturer assigned the students to write essays with a theme related to social justice in today's society. The class was divided into 5 groups with a different sub-theme for each group. The stages of teaching and learning were selection, planning, development, and presentation. By creating the projects, the students had the experience to develop 21st-century skills.